Students with Disabilities - for Themselves, for Others - Paszkowicz, Maria Agnieszka; Garbat, Marcin (Studia Oeconomica Posnaniensia, 2015)
The article presents the social activities of adults with disabilities based on the example of the student community of the University of Zielona Góra. Students with disabilities on the one hand, receive a lot from the university themselves, and on the other they can also contribute a lot to others . Thus they are not just passive recipients of support, but also donors. Being in the area of higher education they not only learn for their own benefit, but they also learn how to live and how to be socially sensitive.